Implementation of Role-Playing Strategies in Increasing Maharah Kalam in State Universities - Chairani, Ully Shifa; Fitriani, Laily (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
Maharah Kalam learning in PKPBA at the Faculty of Science and Technology. Arabic learning activities for five consecutive days, from Monday to Friday, make students bored and tired. So, to minimize these problems, variations, and innovations applied by teachers are needed to encourage students to be more communicative in using Arabic. The goal of this study is to understand how the implementation of role-playing strategies (Role Play) improves Maharah Kalam. This study is descriptive qualitative research which is to illustrate, describe, interpret, explain also answer in more detail the problems to be studied by studying as much as possible an individual, a group, or an event. The data collection method in this study is observation. The population in this study were all PKPBA students of Faculty of Science and Technology 2 and the sample in this research were all PKPBA students of Faculty of Science and Technology 2 totaling 40 people. Data analysis techniques used in this study include conclusion drawing, namely concluding also verification. The results of the implementation of the application are designed through 3 stages, namely: (1) Introduction which includes greetings then asking how are you to explain the learning scenario with role-playing strategies, (2) Core which includes the implementation of learning using role-playing strategies per group, and (3) closing which includes learning evaluation.   Keywords: Maharah Kalam, Arabic Language Learning, Role-Playing Strategies